2002
DOI: 10.1089/105072502760339370
|View full text |Cite
|
Sign up to set email alerts
|

Independent Involvement of CD8+CD25+Cells and Thyroid Autoantibodies in Disease Severity of Hashimoto's Disease

Abstract: Hashimoto's disease (HD) is well known as an autoimmune thyroid disease caused by the destruction of the thyroid follicles, and can be diagnosed in the subclinical stage with thyroid-specific autoantibodies. However, some patients with HD develop hypothyroidism and are treated with thyroxine (severe HD), but most do not throughout their lives (mild HD). To clarify the immunologic differences between these two groups of patients with HD, we examined serum thyroid autoantibodies (antithyroid peroxidase antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
37
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 37 publications
12
37
0
5
Order By: Relevance
“…Immune differences that underlie differences in the severity and intractability of these diseases remain unclear, and disease severity and intractability are difficult to predict. However, we have shown that particular lymphocyte subsets [4][5][6][7] and serum soluble CD8 [8] are related to the severity and intractability of these diseases. The levels of TSH receptor antibody (TRAb), IL-4, and IgE are also reported as the factors involved in the prediction of remission in GD [9,10].…”
mentioning
confidence: 98%
“…Immune differences that underlie differences in the severity and intractability of these diseases remain unclear, and disease severity and intractability are difficult to predict. However, we have shown that particular lymphocyte subsets [4][5][6][7] and serum soluble CD8 [8] are related to the severity and intractability of these diseases. The levels of TSH receptor antibody (TRAb), IL-4, and IgE are also reported as the factors involved in the prediction of remission in GD [9,10].…”
mentioning
confidence: 98%
“…Because the +874T allele is associated with high production of IFN-γ [6], which activates cytotoxic T lymphocytes [4], our present findings also suggest that activation of cytotoxic T lymphocytes may be increased in patients with severe HD. Indeed, we previously reported that the proportion of activated cytotoxic T lymphocytes is increased in patients with severe HD [3]. Previous studies have also shown that IFN-γ levels are increased in some patients with HD [8,9] and that intracellular expression of IFN-γ in T cells is increased in HD patients with severely destructed thyroid follicles [10].…”
Section: Discussionmentioning
confidence: 85%
“…Although there are previous reports that have examined the association of gene polymorphisms with the development of GD and HD [12][13][14], this is the first study showing the significant association of gene polymorphisms with the severity of autoimmune thyroid diseases. We previously reported that activated cytotoxic T lymphocytes and TgAb are independent factors that contribute to the severity of HD and that the proportion of activated cytotoxic T lymphocytes is high in severe HD patients negative for serum TgAb but not in severe HD patients positive for TgAb [3]. These findings are also consistent with our present findings that the frequency of the T allele of IFN-γ was higher in patients with severe HD negative for TgAb but not in patients with severe HD positive for TgAb (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HT the Th1 cell response prevails with predominant production of IFN-, IL-2 and TNF- (Fisfalen, Palmer et al, 1997;Fisfalen, Soltani et al, 1997;Watanabe, Yamamoto et al, 2002). The Th2 humoral response pertains to GD with production of cytokines IL-4, IL-5, IL-6, IL-10 and IL-13 and suppression of INF- (Yano, Sone et al, 1995;Abbas Murphy et al, 1996;Fisfalen, Palmer et al, 1997;Fisfalen, Soltani et al, 1997).…”
Section: Immunity and T Cells 21 Inflammatory Response In Autoimmunementioning
confidence: 99%